2011
DOI: 10.1097/ccm.0b013e318206b80f
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of intravascular and surface cooling techniques in comatose cardiac arrest survivors*

Abstract: In this study, surface and core cooling of out-of-hospital cardiac arrest patients following the same established postresuscitation treatment protocol resulted in similar survival to hospital discharge and comparable neurologic function at follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(96 citation statements)
references
References 33 publications
4
88
1
3
Order By: Relevance
“…Recently, it has been reported that there are no differences in temperature management between automatic surface and core cooling devices. 17 Another factor that may have had an impact on the better results in patients assigned to 32°C was that this group of patients remained cooled for a longer period of time than those assigned to 34°C. Although the duration at target temperature was similar in both groups, patients assigned to 32°C required more time to reach the target temperature, as well as a longer rewarming time.…”
Section: Lopez-de-sa Et Al Two Hypothermia Levels Post Cardiac Arrestmentioning
confidence: 99%
“…Recently, it has been reported that there are no differences in temperature management between automatic surface and core cooling devices. 17 Another factor that may have had an impact on the better results in patients assigned to 32°C was that this group of patients remained cooled for a longer period of time than those assigned to 34°C. Although the duration at target temperature was similar in both groups, patients assigned to 32°C required more time to reach the target temperature, as well as a longer rewarming time.…”
Section: Lopez-de-sa Et Al Two Hypothermia Levels Post Cardiac Arrestmentioning
confidence: 99%
“…Although firm answers are missing, some provocative findings are reported. In a head-tohead, single center, observational comparison of 167 patient receiving either the CoolGard (Zoll Circulation, Chelmsford, Massachusetts) or Arctic Sun (Medivance, Louisville, Colorado) systems, no significant differences were found in the rate of cooling, ICU stay, duration of mechanical ventilation, survival to discharge, survival at 6-12 mo, of neurologic outcomes [222] . Of note, more hypomagnesemia was observed in the endovascular group.…”
Section: Logistics Of Deliverymentioning
confidence: 99%
“…Head-to-head comparisons of surface and endovascular cooling devices after cardiac arrest have revealed similar cooling efficacy and numbers of adverse effects, except that the surface group experienced more hyperglycemia, whereas the endovascular group experienced more hypomagnesemia [87]. Although it has been proposed that catheter cooling may result in less shivering [75], this study did not show any difference in the rate of shivering between the 2 methods [87].…”
Section: Intravascular Cooling Cathetersmentioning
confidence: 50%
“…Although it has been proposed that catheter cooling may result in less shivering [75], this study did not show any difference in the rate of shivering between the 2 methods [87]. The study was not sufficiently powered to find a difference in survival or neurological outcome.…”
Section: Intravascular Cooling Cathetersmentioning
confidence: 56%